Capacidade combinatória e desempenho de híbridos de sorgo sacarino (Sorghumbicolor L. Moench.) com aptidão para produção de biomassa e etanol - Pereira, Danilo Alves (2020)
The sweet sorghum is a bioenergy crop mainly used in the production of first-generation ethanol. Plant breeding in Brazil has sought the enlargement of the national supply of ethanol and also the flexibilization the ideotype of this crop aiming to produce hybrids with high biomass yield, with or without photoperiod sensitivity. This strategy implies to an economic diversification allowing the improvement on the power energy generation ability from sweet sorghum. Thus, this study aimed to estimate the general (GCA) and specific (SCA) combining ability of male-sterile (A) and restorer (R) lines of sweet sorghum to produce hybrids with high performance for ethanol and biomass yield. A total of 30 hybrids were obtained from a partial diallel cross of six A-lines with high sugar content in stalk juice, and five R-lines. These genotypes were evaluated for flowering time (FT), plant height (PH), fresh biomass yield (FBY), juice extractability percentage (EXT), total soluble solids (TSS), and tons of Brix per hectare (TBH). The 30 hybrids and six checks were tested in two environments in Minas Gerais State of Brazil. The experimental hybrids diverged for most traits across environments, although only a few hybrids were superior in performance to the checks. The A-lines had a significant estimate of GCA for the traits EXT, TSS, and TBH, whereas the R-lines were significant for all traits. The hybrids with the best scores in the multitrait index were those that had the CMSX5022 as the male genitor, which is a dry stem genotype and sensitive to photoperiod. There was no significant SCA for the traits EXT, FBY, TSS, and TBH. Regarding sugar yield (TBH), photoperiod-sensitive and non-sensitive genotypes were best ranked. Whereas for biomass yield (FBY), photoperiod-sensitive hybrids had a clear advantage. Therefore, photoperiod sensitivity is an important feature of sweet sorghum genotypes with high biomass production. The best ranked hybrids were CMSXS5506 x CMSX646 (non-sensitive) and CMSXS5507 x CMSX5022 (sensitive to photoperiod). Although, no heterosis was found to traits related to ethanol and biomass yield.